Daily rhythmicity of high affinity copper transport - Perea-García, Ana (Plant Signal Behav, 2016)
A differential demand for copper (Cu) of essential cupro-proteins that act within the mitochondrial and chloroplastal electronic transport chains occurs along the daily light/dark cycles. This requires a fine-tuned spatiotemporal regulation of Cu delivery, becoming especially relevant under non-optimal growth conditions. When scarce, Cu is imported through plasma membrane-bound high affinity Cu transporters (COPTs) whose coding genes are transcriptionally induced by the SPL7 transcription factor. Temporal homeostatic mechanisms are evidenced by the presence of multiple light- and clock-responsive regulatory cis elements in the promoters of both SPL7 and its COPT targets. A model is presented here for such temporal regulation that is based on the synchrony between the basal oscillatory pattern of SPL7 and its targets, such as COPT2. Conversely, Cu feeds back to coordinate intracellular Cu availability on the SPL7-dependent regulation of further Cu acquisition. This occurs via regulation at COPT transporters. Moreover, exogenous Cu affects several circadian-clock components, such as the timing of GIGANTEA transcript abundance. Together we propose that there is a dynamic response to Cu that is integrated over diurnal time to maximize metabolic efficiency under challenging conditions.